Making the invisible visible: a systematic review of sexual minority women's health in Southern Africa - Alexandra Muller; Tonda L. Hughes (BMC, 2016)
Abstract Background Over the past two decades research on sexual and gender minority (lesbian, gay, bisexual and transgender; LGBT) health has highlighted substantial health disparities based on sexual orientation and gender identity in many parts of the world. We systematically reviewed the literature on sexual minority women's (SMW) health in Southern Africa, with the objective of identifying existing evidence and pointing out knowledge gaps around the health of this vulnerable group in this region. Methods A systematic review of publications in English, French, Portuguese or German, indexed in PubMed or MEDLINE between the years 2000 and 2015, following PRISMA guidelines. Additional studies were identified by searching bibliographies of identified studies. Search terms included (Lesbian OR bisexual OR "women who have sex with women"), (HIV OR depression OR "substance use" OR "substance abuse" OR "mental health" OR suicide OR anxiety OR cancer), and geographical specification. All empirical studies that used quantitative or qualitative methods, which contributed to evidence for SMW's health in one, a few or all of the countries, were included. Theoretical and review articles were excluded. Data were extracted independently by 2 researchers using predefined data fields, which included a risk of bias/quality assessment. Results Of 315 hits, 9 articles were selected for review and a further 6 were identified through bibliography searches. Most studies were conducted with small sample sizes in South Africa and focused on sexual health. SMW included in the studies were racially and socio-economically heterogeneous. Studies focused predominately on young populations, and highlighted substance use and violence as key health issues for SMW in Southern Africa. Conclusions Although there are large gaps in the literature, the review highlighted substantial sexual-orientation-related health disparities among women in Southern Africa. The findings have important implications for public health policy and research, highlighting the lack of population-level evidence on the one hand, and the impact of criminalizing laws around homosexuality on the other hand.